Underwater acoustic OFDM channel equalization based on virtual time reversal mirror - Yan-ling YIN; Gang QIAO; Song-zuo LIU (Tongxin xuebao, 2015)
To solve the problem of the severe inter-symbol interference of orthogonal frequency division multiplexing (OFDM) communication caused by underwater acoustic multipath channel,a virtual time reversal channel equalization scheme was proposed.VTRM was able to shorten the channel impulse response and alleviate the phase distortion caused by the acoustic channel for its characteristic of the temporal compression and phase conjugation in frequency domain.The matching pursuit (MP) algorithm was applied to estimate the channel impulse response which could estimate the channel amplitude,time delay and phase accurately.It provided the channel information for the VTRM channel equalization.It also improved a lot compared to the traditional matching correlation channel estimation method which couldn't estimate the channel phase and the estimation precision was low.The simulation,pool trail and Songhua lake experiment show that the performance of VTRM channel equalization is better than that of the PTRM and LS channel equalization in the OFDM underwater acoustic communication.